Anti-inflammatory and analgesic effects of lipid extract from Eryx snakes in adjuvant-induced arthritis in rats - Khakimov, Ziyovuddin Z.; Rakhmanov, Alisher K.; Akbarov, Umidbek S. (International Journal of Basic & Clinical Pharmacology, 2026)
Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease in which long-term use of standard anti-inflammatory drugs is limited by incomplete efficacy and adverse effects, creating a need for safer alternative agents from natural sources. This study evaluated the prophylactic effect of a lipid extract obtained from Eryx snakes (LEES) in a rat model of adjuvant-induced arthritis (AIA). Methods: Arthritis was induced in male rats by sub-plantar injection of Complete Freund’s Adjuvant (CFA). Animals received daily oral administration of LEES (50 mg/kg), diclofenac (10 mg/kg), or indomethacin (4 mg/kg) for 13 days. The therapeutic effects were assessed by monitoring paw edema, local hyperthermia, and pain sensitivity (Hargreaves test) over 14 days. Results: LEES administration significantly suppressed paw edema, achieving 45.6% inhibition by day 14, and effectively attenuated local hyperthermia. The extract also demonstrated significant analgesic activity by preserving thermal withdrawal latency and mitigated inflammation-associated body weight loss. Notably, the therapeutic efficacy of LEES was comparable to that of the reference NSAIDs, diclofenac and indomethacin. Conclusions: The study confirms that LEES effectively mitigates clinical signs of chronic arthritis with an efficacy profile similar to diclofenac and indomethacin. Thus, LEES represents a viable natural candidate for the development of novel anti-inflammatory agents.